The way things work. Engines [videorecording (DVD)] - Zamora, Diego; Macaulay, David (Schlessinger Media, 2003)
The Mammoth Islanders are looking for an alternative to using mammoths to deliver their pizzas so they experiment with different internal combustion engines, from rockets to turbofan jet engines to gasoline engines. By comparing the advantages and drawbacks of these engines, they determine which one will serve their business best and ensure that the pizzas are delivered on time.